Microscopy and single molecule detection in photosynthesis - Vacha, Frantisek; Bumba, Ladislav; Kaftan, David; Vacha, Martin (Micron (Oxford, England, 2005)
Progress in various fields of microscopy techniques brought up enormous possibilities to study the photosynthesis down to the level of individual pigment-protein complexes. The aim of this review is to present recent developments in the photosynthesis research obtained using such highly advanced techniques. Three areas of microscopy techniques covering optical microscopy, electron microscopy and scanning probe microscopy are reviewed. Whereas the electron microscopy and scanning probe microscopy are used in photosynthesis mainly for structural studies of photosynthetic pigment-protein complexes, the optical microscopy is used also for functional studies.
Keywords: světlosběrné proteinové komplexy; Photosynthesis; spektrální analýza; Microscopy; fotosystém II (proteinový komplex); Light-Harvesting Protein Complexes; Microscopy, Electron; Photosystem II Protein Complex; Spectrum Analysis; mikroskopie; krystalografie; fotosyntéza; fotosystém I (proteinový komplex); Photosystem I Protein Complex; elektronová mikroskopie; Crystallography